Febrile neutropenia in oncohematological patients: a bibliographic review on bacteriological profle and resistance in Latin America - Mercado González, Andrés Felipe (2022)
Objective. To describe febrile neutropenia in oncohematological patients in Latin America, its bacteriological profle and resistance.  Methods. A systematic review study was carried out, following PRISMA  criteria in order to respond to the research objective. Information was  collected from observational studies,  review articles, meta-analysis,  systematic reviews, in English and Spanish. The review was carried out in the LILACS, PubMed, ScienceDirect and SciELO databases, using Medical Subject Headings (MeSH) terms and health sciences descriptors (DeCS) for the search strategy. Results. A total of 9 articles were selected, showing that the predominant germs associated  with patients with febrile neutropenia are gram-negative bacilli, with  Escherichia coli being the main and  least resistant. On the other hand, Klebsiella pneumoniae and  Pseudomona aeruginosa are more resistant gram-negative  microorganisms, causing more severe infection. The antimicrobials with good efcacy and absence of resistance  against these pathogens are  carbapenemics, amikacin, meropenem and tigecycline. Staphylococcus aureus and Staphylococcus epidermidis are the main grampositive agents found, with a wide resistance and 100% sensitivity to linezolid, daptomycin and vancomycin. Conclusions. Colombia is the country with the highest antimicrobial resistance in Latin  America. However, there is an increase in resistant bacteria over time, due to  incorrect use of antimicrobials,  omission of microbiological examinations and lack of scientifc evidence; therefore, it is important to carry out quantitative microbiological studies in Latin American countries in order to establish empirical treatment  with good results.